The Representation, Generalized Binet Formula and Sums of The Generalized Jacobsthal p-Sequence - Ahmet Daşdemir (Hittite Journal of Science and Engineering, 2016)
In this study, a new generalization of the usual Jacobsthal sequence is presented, which is called the generalized Jacobsthal Binet formula, the generating functions and the combinatorial representations of the generalized Jacobsthal p-sequence are investigated. Moreover, certain sum formula consisting of the terms of the generalized Jacobsthal p-sequence are given